Educating Immigrants – Educating about Immigrants: Suburban Social Housing as a Knowledge Hub for Danish Welfare-State Integration Politics 1970s–1980s - Buchardt, Mette (Nordic Journal of Educational History, 2026)
The social housing project Ishøj-Planen and the surrounding suburban municipality Ishøj, south of the Danish capital, became from the 1970s a site for de facto production of policy about immigrants at a time when central policy was scarce. This included a double knowledge transmission and production process: municipal authorities and housing associations educated immigrants about welfare-state procedures such as school attendance, the tax system, the labour market, and housing rules. Simultaneously, data about immigrants were collected, policies and practices from other states were studied, and knowledge-seeking students and scholars were received and facilitated. Based on this case, and combining history of education and knowledge perspectives with frontline theory, the article explores suburban social housing 1970s–1980s as a hub for knowledge production on “immigrants” and how to “educate them” to the welfare state and discusses how this possibly fed into establishing problem definitions and policy.